DEVELOPMENT OF THE MECHANISM FOR FINANCING CULTURAL INSTITUTIONS - G. N. Kutsuri (Вестник университета)
The problematic issues of financing cultural institutions have been considered. A study of the current state of the funding mechanism for cultural institutions from the perspective of the European model with its emphasis on their state financial support has been conducted. The problems of functioning of the mechanism of financing cultural institutions both in terms of state allocations for the implementation of state tasks and income from business activities have been identified. The methods and tools of the mechanism for financing cultural institutions in Russia have been evaluated. Attention on the shortcomings of the modern legal framework regulating patronage and sponsorship as a tool for forming financial resources of cultural institutions, – has been focused. The directions of development of the mechanism of financial support of cultural institutions taking into account domestic and international experience have been suggested.